การใช้บึงประดิษฐ์แบบน้ำไหลใต้ผิวดินเพื่อการบำบัดขั้นที่สามสำหรับน้ำชะมูลฝอย - วรากร เกิดทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Studies surface-flow constructed wetlands in treating landfill leachate that discharge from stabilization pounds. Three laboratory-scale sand bed constructed wetlands were used for treatment efficiency comparison. Two kind of plants, cattails (Typha angustiolia) and sea holly (Acanthus ebracteatus), was planted in each wetland while no plant wetland was a control unit. Each unit was feed 500 mg./l. COD influent at three hydraulic loading rate; 3.3, 2.2 and 1.1 cm./d.. The experimental results revealed that the treatability was invert with hydraulic loading rate. Sea holly planted wetland and control unit have the same treatment efficiency at each hydraulic loading rate while the cattial unit was higher treatability than. The cattials planted constructed wetlands at 1.1 cm./d. hydraulic loading rate is the most effective treatability while the removal efficiencies of SS, COD, true color (SU) and total nitrogen were 92%, 68%, 65% and 89% respectively. Nitrogen balance was revealed that 78% of nitrogen was removed by dinitrification in sand bed.